Preços de commodities agrícolas e o comportamento de mercado invertido (backwardation): o caso da soja - Sykora, Nelson Danilo (2013)
The relationship between spot and future market and commodity price Backwardation have had an emphasis on the literature of economics and finance. The aim of this paper is to present the main causes responsible for the behavior of Backwardation and to identify the properties that characterize the equilibrium in agricultural commodit y prices. Be the existence of risk premium or the convenience yield, the unders tanding of the effects on the replication of future price and on the term structure of commodity prices remains an open issue. On the other hand, t he p remise of perfect p ortfolio replication and the absence of market frictions imply that the understanding of c ommodity price Backwardation comes from the understanding of the stochastic process of the underlying asset itself . The risk - neutral pricing allied with signs of reversion in prices supports pricing models such as Schwartz and Smith (2000), whose calibration and results will be presented for soybeans.